Study of the remanufacturing critical threshold and remanufacturability evaluation for FV520B-I blade based on fatigue life and FEA. (May 2020) - Jinlong, Wang; Jing, Yu; Yuxing, Yang; Fengming, Du; Jingsi, Wang
Graphical abstract: Considering the effect of fatigue failure on the remanufacturability evaluation, the definition and quantitative model of the remanufacturing critical threshold are proposed based on the qualitative relationship between the fatigue life and remanufacturing requirements. Taking the existing remanufacturing evaluation system as reference, two new remanufacturability evaluation indexes and the remanufacturability evaluation function are proposed, to evaluate the remanufacturability of FV520B-I blade based on fatigue life. Furthermore, the new remanufacturing evaluation method based on fatigue life is proposed by integrating fatigue life prediction and remanufacturability evaluation together. Highlights: First, a new fatigue life prediction model for FV520B-I blade with fatigue crack is proposed. Second, remanufacturing critical threshold and parameter are proposed and modeled. Third, two specific remanufacturing evaluation indexes for FV520B-I blade are proposed. Fourth, a new method of remanufacturability evaluation based on fatigue life is proposed. Abstract: This paper focused on determining the remanufacturing critical threshold, exploring new remanufacturability evaluation method based on fatigue life and FEA, which are the key issues for the remanufacturing research of FV520B-I compressor blade. With the comprehensive application of finite element analysis (FEA) and fracture mechanism, the stress distribution of the blade in the operating condition is analyzed, and the fatigue life model of FV520B-I blade is established. Considering the effect of fatigue failure on the remanufacturability evaluation, the definition and quantitative model of the remanufacturing critical threshold are proposed based on the qualitative relationship between the fatigue life and remanufacturing requirements. Taking the existing remanufacturing evaluation system as reference, two new remanufacturability evaluation indexes and the remanufacturability evaluation function are proposed, to evaluate the remanufacturability of FV520B-I blade based on fatigue life. Furthermore, the new remanufacturing evaluation method based on fatigue life is proposed by integrating fatigue life prediction and remanufacturability evaluation together, which is difficult in theory but valuable in actual engineering, and also makes a contribution to guarantee the safety of remanufactured FV520B-I blade in operational condition.